In an arid urban matrix, fragment size predicts access to frugivory and rain necessary for plant population persistence. Issue 6 (21st June 2016) - Ness, J. H.; Pfeffer, M.; Stark, J.; Guest, A.; Combs, L. J.; Nathan, E.
Abstract: Cities annex wilderness and alter the interactions between the plant and animal assemblages embedded in the remaining nature fragments. Here, we explore consequences of habitat fragmentation for dispersal of cactus by fruit‐eating mammals in the Sonoran Desert landscape. We use the barrel cactus, Ferocactus wislizeni, as a model system to diagnose (1) how fruit utilization by a mammal assemblage changes with fragment area and isolation, (2) what characteristics make individual plants particularly susceptible to frugivore failure, and (3) how inter‐fragment differences in plant–frugivore interactions influence the seedlings' susceptibility to other stressors (granivores and drought). We described the type and phenology of plant–animal interactions in 20 fragments along a 0.05–500 ha size continuum within a large city (Tucson, Arizona, USA), and combined allometric scaling models of mammalian home ranges and descriptions of plant size distributions to predict the fraction of the fruit crops accessible to resident mammalian frugivores in each fragment. Fruit removal rates generally increased along a continuum of fragment sizes, and older, taller plants were particularly susceptible to frugivore failure and more likely to have fruits attacked by granivorous rodents. As a result, thresholds where the nature and/or phenology of a plant's interactions with animals changes can be accurately predicted by integrating descriptions of fragment size, fragment isolation, and plant population structure. Last, we found support for the hypothesis that fragmentation‐induced changes in the phenology of fruit removal compromise the seedlings' ability to exploit precipitation delivered in winter and spring. Specifically, as a result of slower fruit removal, the seed crops in small fragments forfeit access to an increasing proportion of the rains between October and March, which determine whether cactus seedlings can survive the following dry season (April, May, June). We expect these inter‐site differences in the type and phenology of interactions to compromise the integrity of plant populations in smaller fragments, to become increasingly influential in ecological settings in the Sonoran Desert where access to precipitation is essential, and to become increasingly prevalent as the plants in newly fragmented plant populations age (grow) to sizes that are more susceptible to frugivore failure in the defaunated landscapes.